2017
DOI: 10.1101/235598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular insights intoVibrio cholerae’s intra-amoebal host-pathogen interactions

Abstract: Vibrio cholerae, which causes the diarrheal disease cholera, is a species of bacteria commonly found in aquatic habitats. Within such environments, the bacterium must defend itself against predatory protozoan grazers. Amoebae are prominent grazers, with Acanthamoeba castellanii being one of the best-studied aquatic amoebae. We previously showed that V. cholerae resists digestion by A. castellanii and establishes a replication niche within the host’s osmoregulatory organelle. In this study, we deciphered the mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…The T6SS of pandemic V. cholerae is silent under standard laboratory conditions (Pukatzki et al ., ). In contrast to pandemic strains, the O37 serogroup strains V52 and ATCC25872 are toxigenic but nonpandemic and their T6SS is constitutively activated, as is the case for most environmental isolates (Pukatzki et al ., ; Unterweger et al ., ; Bernardy et al ., ; Van der Henst et al ., ). To explain the differences in T6SS activity and to provide insight into the T6SS's biological functions, it is, therefore, important to understand the underlying regulatory pathways in pandemic V. cholerae strains.…”
Section: Introductionmentioning
confidence: 97%
“…The T6SS of pandemic V. cholerae is silent under standard laboratory conditions (Pukatzki et al ., ). In contrast to pandemic strains, the O37 serogroup strains V52 and ATCC25872 are toxigenic but nonpandemic and their T6SS is constitutively activated, as is the case for most environmental isolates (Pukatzki et al ., ; Unterweger et al ., ; Bernardy et al ., ; Van der Henst et al ., ). To explain the differences in T6SS activity and to provide insight into the T6SS's biological functions, it is, therefore, important to understand the underlying regulatory pathways in pandemic V. cholerae strains.…”
Section: Introductionmentioning
confidence: 97%
“…cholerae exerted a tight regulation over this toxin and thereby successfully infected the amoebae's contractile vacuole, constitutive hemolysin activity by the environmental isolates killed the host prematurely, preventing the formation of this replication niche (Van der Henst et al, 2018). We speculated that hemolysin activity could also be involved in the resistance against D. discoideum grazing that we observed for the environmental strains from clades C and D. To follow up on this hypothesis, we first tested all environmental WT strains for hemolysis on blood agar plates.…”
Section: Enhanced Hemolysin Production In Environmental V Cholerae Dmentioning
confidence: 99%
“…Notably, V. cholerae's T6SS was initially discovered due to its anti-eukaryotic activity that allowed the non-pandemic V. cholerae strain V52 to avoid predation by D. discoideum (Pukatzki et al, 2006). Indeed, previous studies had indicated that, in contrast to the 7 th pandemic strains, non-pandemic toxigenic V. cholerae (such as the two O37 serogroup strains V52 and ATCC25872; Pukatzki et al, 2006;Basler et al, 2012;Van der Henst et al, 2018) as well as environmental isolates (Unterweger et al, 2012;Bernardy et al, 2016;Crisan and Hammer, 2020) maintain constitutive T6SS activity. This is in contrast to the silenced T6SS of pandemic strains, which are primarily induced by chitin or low c-di-GMP levels, concomitantly with natural competence and the production of extracellular enzymes, respectively (Borgeaud et al, 2015;Watve et al, 2015;Veening and Blokesch, 2017).…”
Section: Environmental Isolates Constitutively Produce T6ssmentioning
confidence: 99%
See 2 more Smart Citations